Label-free single-cell RNA multiplexing leveraging genetic variability - Konrad Hoeft; Tore Bleckwehl; David Schumacher; Hyojin Kim; Robert Meyer; Qingqing Long; Ling Zhang; Christian Möller; Marian C. Clahsen-van Groningen; Anne Babler; Turgay Saritas; Ingo Kurth; et al. (Nature Communications)
Abstract Single cell RNA sequencing has provided unprecedented insights into the molecular cues and cellular heterogeneity underlying human disease. However, the high costs and complexity of single cell methods remain a major obstacle for generating large-scale human cohorts. Here, we compare current state-of-the-art single cell multiplexing technologies, and provide a widely applicable demultiplexing method, SoupLadle, that enables simple, yet robust high-throughput multiplexing leveraging genetic variability of patients.